Zones of entrapment and impunity: on the constitution of vague and strange regimes of power - Hallsworth, Simon (Critical criminology, 2022)
This article challenges a tendency prominent in critical theory - one that holds that being "vague and strange" constitute qualities of life opposed to the grid-like systems of coercive control intrinsic to the operation of modern power regimes which, by their ascriptive nature, are compelled to suppress all life which exhibits these traits. Consequently, vagueness represents not only the antithesis of modern power, but a source of resistance against it. This article contests this assumption by exploring the vague regimes of power (which, following William Burroughs, we call "interzones"), which also exist within the fabric of the administered order. The article examines how these interzones function and explores two incarnations: zones of entrapment and zones of impunity.